ОСОБЛИВОСТІ ФОРМУВАННЯ БАГАТОКАНАЛЬНИХ ІМПУЛЬСНИХ СТРУМІВ І ШВИДКО МІГРУЮЧИХ ЕЛЕКТРОІСКРІНЬ В ШАРІ СТРУМОПРОВІДНИХ ГРАНУЛ ЕЛЕКТРОРОЗРЯДНИХ УСТАНОВОК - Щерба, А.А.; Супруновська, Н.І.; Щерба, М.А. (Інститут електродинаміки НАН України, Київ, 2022)
The paper reveals the electro-physical features of the formation of multi-channel pulse currents and fast-migrating electric sparks in the layer of current-conductive granules of electric-discharge installations (EDIs) with reservoir capacitors. Such features make it possible to increase many times the productivity of the electric-spark dispersion of metal granules during single discharge current of reservoir capacitors, which flows between the electrodes of EDIs. Theoretical substantiation and experimental confirmation of multi-channel spark discharges in the layer of conductive granules are presented. The influence of the capacitance and charge voltage of reservoir capacitors on the nature of transient processes in the discharge circuit of the EDIs is investigated. The dependence of the effective value of the active load resistance of the EDIs on the value of the pre-charge voltage of its reservoir capacitors and the value of its capacitances has been experimentally determined. It is proved that an increase in the averaged Q-factor of the discharge circuit with an increase in the charge voltage of the capacitor bank of EDI is caused by a decrease in the effective value of the active resistance of the layer of metal granules when spark-generating discharge currents flow through it. References 16, Figures 7.